2016
DOI: 10.1186/s13020-016-0116-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of trans-ferulic acid on proliferation and migration of human lung cancer cells accompanied with increased endogenous reactive oxygen species and β-catenin instability

Abstract: BackgroundTrans-ferulic (FA) acid exhibits antioxidant effects in vitro. However, the underlying mechanism of trans-FA activity in cellular physiology, especially cancer physiology, remains largely unknown. This study investigated the cellular physiological effects of trans-FA on the H1299 human lung cancer cell line.MethodsThe 2,2-diphenyl-1-picrylhydrazyl assay was used to determine free radical scavenging capability. Assessment of intracellular reactive oxygen species (ROS) was evaluated using oxidized 2ʹ,7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Increased ROS production is considered to be an important factor controlling cell survival and apoptosis [18][19][20]. The effect of OPE on ROS generation was examined using DCFH-DA staining.…”
Section: The Effect Of Ope On Ros Of Liver Cancer Cellsmentioning
confidence: 99%
“…Increased ROS production is considered to be an important factor controlling cell survival and apoptosis [18][19][20]. The effect of OPE on ROS generation was examined using DCFH-DA staining.…”
Section: The Effect Of Ope On Ros Of Liver Cancer Cellsmentioning
confidence: 99%
“…In addition to ROS and mitochondrial function, we also evaluated the effects of DOPA-1 treatment on apoptosis-related protein expression. As a major modulator of apoptosis, the Bcl-2 protein family controls the release of mitochondrial apoptosis-inducing factors [ 31 ], which can be divided into pro-apoptotic proteins (such as Bax, Bak, and Bid) and anti-apoptotic proteins (such as Bcl-2, Bcl-xL, and Bcl-w) [ 32 ]. In this study, we found that DOPA-1 decreases Bcl-2 expression, while increasing Bax expression in HepG-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The sources of the chemical compounds were either synthetic, or from a plant other than Glinus oppositifolius. Several chemical compounds like benzoic acid [47], trans-ferulic acid [48][49][50][51], vanillin [52], stigmasterol [53], spinasterol [54,55], β-sitosterol [56][57][58][59][60][61][62][63][64][65][66][67][68], vitexin [69], vicenin [70], kaempferol [71] showed anti-cancer effects against breast cancer cell lines, prostate cancer cell lines, colon cancer cell lines, stomach cancer cell lines, leukaemia (Table 1). β-sitosterol acts through down-regulation of Bcl-2 and upregulation of Bax, thereby causing caspase 3 cleavage and PARP cleavage and thereby causes apoptosis (Figure. (Table 2).…”
Section: Pharmacological Activities Of Pure Compounds (Reported Fromgmentioning
confidence: 99%